Microencapsulation with chitosan by spray drying for industry applications - A review - Berta Nogueiro Estevinho (2013)
This work reviews the relevant information about the possibility of producing microparticles with chitosan, by a spray drying process, for industrial applications. The applicability and the advantages of chitosan and modified chitosan in the microencapsulation process are discussed, with special emphasis on relevant operational spray drying conditions, which affect the performance of the final product, namely the efficiency and yield of the microencapsulation process, the particle properties, like size, moisture and stability, and the release time of active compounds. The fundamental equations governing the controlled release of active compounds and the application of control led release technology in food systems are presented.